Development of gamification-based interactive multimedia application for object recognition in children - Taufiqurrochman, Taufiqurrochman; Nurlaela, Lela; Hasibuan, Tuhfatul Habibah; Suryantoro, Hari; Kurniati, Ike (Jurnal Info Sains : Informatika dan Sains, 2024)
The ability to identify items in the environment is a crucial element of cognitive development and early education in children. Nevertheless, there are still constraints in the advancement of specialised applications for the identification of nearby items in youngsters using a gamification methodology. Furthermore, there remains a deficiency of programmes specifically tailored to children, lacking features such as user interfaces that are child-friendly and content that is age-appropriate. This study employs the Research and Development (R&D) methodology, encompassing the phases of analysis, design, development, implementation, and testing. The findings demonstrated that incorporating gamification into interactive multimedia introductions to surrounding objects in children serves as an alternative educational medium that can assist teachers in the teaching and learning process. Specifically, it aids in explaining the identification and description of objects. By employing gamification through practice questions, it effectively stimulates children, enhancing their comprehension and proficiency in recognising surrounding objects. The comprehensive test findings indicate that this application has the potential to serve as an efficient and enjoyable alternative educational medium for children.